2018
DOI: 10.7150/jca.23162
|View full text |Cite
|
Sign up to set email alerts
|

A Real-World Data Study to Evaluate Treatment Patterns, Clinical Characteristics and Survival Outcomes for First- and Second-Line Treatment in Locally Advanced and Metastatic Urothelial Cancer Patients in Germany

Abstract: Background: Worldwide, urothelial carcinoma (UC) is a common cause of morbidity and mortality. In particular, the incidence of bladder cancer varies widely across Europe; Germany has the ninth highest international age-standardized incidence. For advanced UC or metastatic UC (mUC), platinum-based combination chemotherapy is the standard first-line (1L) treatment; however, there is wide heterogeneity of second-line (2L) treatments, ranging from vinflunine in parts of Europe to taxanes and other agents elsewhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
4
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 33 publications
7
36
4
3
Order By: Relevance
“…Just under half of these patients received single-agent weekly paclitaxel. The low uptake of second-line therapy, consistent with previous reports (26), may in part reflect the low response rates and short duration of response associated with these agents (27). Second-line chemotherapy at our center has typically been reserved for fit patients or those with symptomatic disease progression and following careful FIGURE 3 | Cox regression analysis comparing cisplatin-based (blue) and carboplatin-based (red) sub-cohorts, adjusted for age, sex, PS, and confirmed metastasis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Just under half of these patients received single-agent weekly paclitaxel. The low uptake of second-line therapy, consistent with previous reports (26), may in part reflect the low response rates and short duration of response associated with these agents (27). Second-line chemotherapy at our center has typically been reserved for fit patients or those with symptomatic disease progression and following careful FIGURE 3 | Cox regression analysis comparing cisplatin-based (blue) and carboplatin-based (red) sub-cohorts, adjusted for age, sex, PS, and confirmed metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…Fisher et al recently reported median OS of 14.6 months with cisplatin and 11.3 months with carboplatin, in a real-world US setting (25). A 16.1 month median OS was reported in a retrospective German study of patients with stage IV UC treated with chemotherapy (26). Whilst the proportion of M1 patients varied between studies, overall our survival is remarkably similar and highlights the need to improve outcomes for this group of patients.…”
Section: Discussionmentioning
confidence: 59%
“…The median survival time for our MUC patients receiving continuous maintenance chemotherapy was 17 months, with no difference between bladder and upper urinary tract cancer location (18 versus 17 months). The survival time was compatible with previous reports (1,13,14). Patient survival was likely related not only to the objective tumor response, but also to inflammation and coagulopathy as major contributory factors to patient death, as demonstrated by the inflammation-related symptoms and cause of death.…”
Section: Discussionsupporting
confidence: 89%
“…Urothelial carcinoma (UC) is the most common cancer of the bladder and upper urinary tract and is invasive and lethal, especially in advanced and metastatic patients (1,2). Advanced UC patients generally have a poor prognosis, and only a few patients survive more than five years (3).…”
Section: Introductionmentioning
confidence: 99%